RETRACTED: Prevention of infections of various genesis in children’s patients: approaches and methods in modern conditions - Pyrchenkova A.S.; Palchaeva A.T.; Zhukova V.S.; Abdullaeva E.N.; Agabekova N.N. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001